Implementasi Konsep Smart Goal Setting Pada Bisnis M-Prod Demi Meningkatkan Business Value - Mohamad Hadi Prasetyo (Universitas Maritim AMNI Semarang, 2023)
Increasing business value for MSMEs is no less important. This community service is carried out with the aim of increasing the business value of M-Prod SMEs which is engaged in convection services. The SMART Goal Setting concept is implemented to make M-Prod have added value and can improve its business performance in the future. This community service program takes the form of a tiered workshop with assistance to the MSMEs concerned so that they focus on profit, not just turnover. This community service is one of the efforts to increase the competitiveness of M-Prod SMEs in order to gain a competitive advantage. The problem faced by business actors is that the specific goals of a business are not measurable. Finally partners do not understand how goals are set and how to analyze a measurable goal. This is very influential in terms of business development, this will have an impact on profits.